Integrating Educational Resources and Leadership for Sustainable Quality in Multidisciplinary Education - Hariyadi, Ahmad (Assyfa Journal of Multidisciplinary Education, 2025)
In today's digital transformation era, 21st-century skills such as critical thinking, creativity, collaboration, and digital literacy have become essential competencies for students. Project-based teaching strategies, technology integration, and collaborative learning have proven effective and engaging in enhancing these skills. This research is motivated by the urgent need to systematically integrate educational resources and leadership in multidisciplinary education, considering that previous studies have primarily evaluated the impact of separate interventions on cognitive and social development, while comprehensive evaluations on cognitive, psychomotor, and affective domains remain limited. The main objective of this study is to examine the synergy between educational resources and leadership practices in achieving sustainable quality through an integration approach in multidisciplinary education. The method employed is mixed-methods, combining qualitative phenomenological analysis through in-depth interviews and document analysis, as well as quantitative meta-analysis of 679 articles indexed from 2005 to 2026, covering levels from elementary to higher education with the use of digital tools for assessment. The study results show a significant positive impact from the integration of educational resources and leadership, with a productivity of 17.6 citations/year, an average impact of 68.5 citations, and a strong correlation between research maturity (r=0.177) and author collaboration (r=0.201) on educational outcomes, while the time of publication has minimal influence (r=-0.177). It is concluded that sustainable educational quality can only be achieved through the strategic integration of educational resources and transformational leadership, with an emphasis on continuous professional development, technology-based pedagogical practices, and multidisciplinary collaboration as the foundation for educational excellence and national development.